Iatrogenic Displacement of a Foreign Body into the Periapical Tissues - Hugo Plascencia; Alvaro Cruz; Rodrigo Solís; Mariana Díaz; Josué Vázquez (Hindawi Limited, 2014)
The presence of a foreign body in the periapical tissues can cause endodontic failure by triggering an inflammatory response and a subsequent foreign body reaction. This inflammatory response, which can occur to varying degrees, appears radiographically as a radiolucency that can remain asymptomatic for many years. A foreign object can reach the apical region by accident or iatrogenic procedures during dental procedures. The aim of the present case report is to describe the endodontic surgical treatment of an iatrogenic displacement of a foreign body (a metal fragment) into the periapical tissues and to describe its clinical and radiographic follow-up over a period of 52 months.